Late side effects of testicular cancer and treatment: a comprehensive review - M. Raheel Khan; Patrice Kearney Sheehan; Ashley Bazin; Christine Leonard; Umair Aleem; Lynda Corrigan; Ray McDermott (Discover Oncology, 2024)
Abstract Testicular cancer is a rare solid organ tumour associated with high cure rates and young age at diagnosis, hence it has a sizeable cohort of survivors worldwide. As it is one of the earliest tumours to be cured, a lot of studies have highlighted the late side effects of cancer and its different treatment modalities including surgery, radiotherapy and chemotherapy. While we are trying to identify the population at higher risk of platinum based chemotherapy and reduce its exposure, cisplatin based regimes remain an important tool to cure testicular cancer. The list of late side effects include a number of fatal and morbid conditions including but not limited to the second malignant neoplasms, cardiovascular disease, hypogonadism, infertility, metabolic syndrome, chronic respiratory disease, renal insufficiency, hearing loss, peripheral neuropathy, infertility and psychological illnesses like stress and anxiety. These complications eventually result in compromised social and economic health as well as lower life expectancy compared to the normal population. This article provides a comprehensive review of the latest data regarding the late side effects in testicular cancer survivors. A review of these conditions can help us develop recommendations and guidelines to improve the morbidity and mortality in survivors of testicular cancer.